(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Arguing the complicated nature of transnational engagements with traditional musical practices, the case study of the Uzbek dutar in California illustrates one way to engage with the past in non-traditional contexts. After introducing the instrument and definitions of tradition, the essay explores the dutar’s musical traditions in Uzbekistan and its ensemblification in the 20th century. Then it turns to the author’s dutar ensemble, the Central Asian Ensemble at the University of California Santa Cruz. By considering how the imposed structure of the American university system combines with pedagogical collaborations with the author’s master teachers (ustozlar), Ruzibi Khodjayeva and Malikahon Ziyaeva, the paper concludes with the possibilities engagement with previously unfamiliar traditional practices provides for students across the university and for international understanding, more broadly.